Perilaku Bullying pada Mahasiswa Berasrama - Simbolon, Mangadar (Faculty of Psychology, Universitas Gadjah Mada, 2012)
Students’ bullying characteristics phenomena has become a concern because educational institution where educative individuals are being train has in fact become a place of bullying. Bullying is an act of hurting someone done by an individual or group. Bullying is not limited to a community or educational institutional, such as a university, as a whole, but it happened in a narrower area that is related to a campus – dormitory. Dormitory, a place conducive for learning is a social laboratory, with an educative, social, moral and regeneration function. Based on the statistical data of bullying cases of university A, released by the office of the student affairs in 2008, it was found out that there are 1 or 2 cases every semester. Bullies usually consist of 1 to 8 students.To know the types of bullying, factors and affects that causes the act on the victims and dormitory community, and efforts of prevention. A qualitative research was done to dig deep into the real picture of bullying. An interview and discussions were done toward 14 reseach subject. Sources and methodology triangular were done to validate the data. Data analysis was done using the open coding steps. Bullying causes factors in university A is the same in general that is seniority factor, imitating the past experiences. Seniors expect themselves to be honored and problem occurred when juniors dishonored them. Bullies bullied because they were once victims, therefore bullying is somehow done as an act of revenge. Bullying acts occurred in dormitory of university A in Bandung. Anti-bullying systems designed by the university are: Religious understanding development, religious teaching implementation, uplifting moral values. Others things done are improving students’ controlling system by the dormitory deans and monitors (dormitory workers). Keywords: bullying, dormitory, students